Improving the organizational and economic support for the development of enterprises in the hospitality industry in the use of information and communication technologies - Petrovska, Iryna; Safronova, Olha; Mital, Оlena; Ometsynska, Nataliia; Moroz, Volodymyr; Vidomenko, Oksana; Lebedynets, Iryna; Shostakovska, Antonina; Maistrenko, Yuliia; Nosyriev, Oleksandr (My University, 2021)
Conceptual foundations of organizational and economic support for the development of enterprises in the hospitality industry have been developed, taking into account the level of use of information and communication technologies. It has been determined that the main results of the influence of information technologies on the hospitality industry are the optimization of business processes, as well as the transformation of the target consumer of hospitality services. The types of information and communication technologies are systematized depending on the direction of the business processes of the cycle of providing hospitality services. It has been substantiated that through the active use of information and communication technologies, hospitality industry enterprises satisfy the needs of customers in full in accordance with modern requirements. The relationship was established between the results of assessing the level of organizational and economic support for the development of information and communication technologies and the strategic choice of enterprises in the hospitality industry. Three types of strategies are identified – information expansion, improvement, retention and further development – depending on the low, medium and high level of development of information and communication technologies, respectively. The directions of increasing the level of development of information and communication technologies of the hospitality industry at different levels are proposed. The developed theoretical and methodological provisions can be useful in the formation of the concept of strategic development of the hospitality industry. The use of the proposed toolkit reflects the results, both quantitatively (increasing demand for hospitality services, improving financial performance, etc.) and in a qualitative form (improving the quality of service, creating a positive image, etc.).
Keywords: hospitality industry; information and communication technologies; digitalization; business processes; millennials; hospitality development strategy; кафедра економіки і права